Methodological Approaches for Workplace Research and Management. - Tagliaro, Chiara; Orel, Marko; Hua, Ying. (Milton : CRC Press LLC, 2023)
This book explores a wide range of methodological approaches to examining various forms of workplace physical environments.
Intro -- Cover Page -- Half-Title Page -- Series Page -- Title Page -- Copyright Page -- Dedication page -- Contents -- Foreword by Rianne Appel-Meulenbroek and Vitalija Danivska -- Preface: Expanding the understanding of methodological approaches for workplace research and management in the new era -- 1 Outlook: Collecting methods for transdisciplinary workplace research and management -- 2 Workplace autoethnography: Exploring the place through aspects of the self -- 3 Affective ethnography: Interpreting body language in the workplace fieldwork -- 4 Digital ethnography: Understanding platform labour from within -- 5 Critical discourse analysis: Studying the symbolic aspects ofÂ workplaces -- 6 Diary studies: Capturing real-time experiences in the workplace -- 7 Cluster analysis: Grouping workers by work location choice -- 8 Stated choice experiments: Identifying workplace preferences and behaviours -- 9 Delphi method: Reaching consensus on workplace performance -- 10 Social network analysis: Studying social interactions and relations in the workplace -- 11 Surveys: Gathering data for workplace post-occupancy evaluation -- 12 Space syntax: Examining human-workplace behavior through isovists and shortest paths -- 13 Journey mapping: Describing the spatial experience of workplace users -- 14 Compendium: Choosing methods for workplace research and management -- 15 Wind-up: On methodological takeaways and the importance of workplace research -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books